Scarlett Baron. The Birth of Intertextuality: The Riddle of Creativity. Routledge, 2020. - Mariaenrica Giannuzzi (Studies in 20th & 21st Century Literature, 2021)
Review of Scarlett Baron. The Birth of Intertextuality: The Riddle of Creativity. Routledge, 2020. 381 pp.
Keywords: intertextuality; comparative literature; post-structuralism; science of the text